The Role of Financial Audits in Strengthening Accountability and Transparency in Funding Management - M Holili; Wus’atul Khoiroh (Al-Qalam Institute, 2023)
This study aims to analyze a review of the role of financial audit in enforcing financing accountability in schools at the madrasah aliyah level. This research is based on the use of audits as an alternative form for budget fund transparency. This study uses a qualitative approach of descriptive type and data collection analysis techniques with interviews. The results of the study show that the importance of financial audits in enforcing financial accountability in educational institutions and the role of internal and external auditors as an integral part of the internal control system of educational institutions, then explain the challenges in the implementation of audits in educational institutions including limited resources, regulatory complexity, resistance to change, and lack of understanding of the importance of financial audits. The implications of the results of the study examine the importance of implementing good financial audit practices and increasing awareness of the importance of transparency and accountability in financial management in educational institutions and strengthening communication and cooperation between internal auditors, external auditors, and school management. The results of this study are expected to provide.